Mutu Beras dan Nasi Jagung Putih Lokal Varietas Anoman 1 dalam Kemasan Edibel dengan Ketebalan Berbeda - Rahmawati Rahmawati; Astri Yaniansah (Institut Pertanian Bogor, 2021)
Rice is a staple food for most Indonesian population. Nowadays, people want staple foods that are not only filling but also do not increase blood sugar concentration (low glycemic index). One of foods that contain higher starch, lower glycemic index, and higher fiber than rice is white corn. The white color of the corn is an advantage because if it is made in grits it can resemble rice. Weakness of white corn is harder than rice. To soften and make it easier to consume, it is coated with an edible packaging made from tapioca. The purposes of this study were to study (1) the quality of dried corn rice from local white corn Anoman 1 variety in edible packaging with packaging thickness of 0.7, 0.9, 1.1, 1.3, and 1.5 mm; (2) the quality of cooked white corn rice produced. The results showed that the thickness of the edible packaging significantly affected (1) the moisture, ash, protein, fat, and carbohydrate contents of dried white corn rice and (2) all parameters of cooked white corn rice (a = 0.05). The best cooked corn rice based on the stickiness test was found in coated dried corn rice with edible packaging with a thickness of 1.5 mm. Characteristics of (1) dried white corn rice contained 11.39% water, 0.21% db ash, 15.23% db protein, 0.53% db fat, 72.64% carbohydrates, 2.11% crude fiber, (2) the quality of cooked of white corn rice were 18.17 g / mm2 stickiness, yellowish color (score 1.1), slightly distinctive aroma of corn (score 2.5), slightly fluffier texture (score 3.4), and rather strong sweet taste (score 2.8). Keywords: edible packaging, local white corn Anoman 1, rice, stickiness, tapioca